Human Resources Policies and Employees’ Attitude: A Study of Federal University of Petroleum Resources, Effurun, Delta State - Godwin Omafuru Demaki; Goddey Ibrighademor (Universitas Mercu Buana, 2023)
This study examined the influence of human resources policies on employees’ attitudes using the Federal University of Petroleum Resources, Effurun, Delta State as a case study. The study used the survey research design and the instrument of data collection was the questionnaire which was administered to two hundred (200) academic and non-academic staff of the Federal University of Petroleum Resources. Data obtained in the survey were analyzed using linear regression technique. It was found that human resource recruitment and selection policy had a significant influence on employees’ attitudes (F-value = 3.246; P-value = 0.003). In addition, we found that human resource staff training and development policy had a significant effect on employees’ attitudes (F-value = 5.017; P-value = 0.026). The study recommends that the management of Nigerian public institutions of higher learning should sustain and improve on their recruitment and selection and staff training and development policies in order to enhance employees’ attitude to work. More so, there is a need for the management of Nigerian public institutions of higher learning to embrace diverse types of human resource policies that will improve employees’ attitudes to work.